2021
DOI: 10.1016/j.hpb.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after resection for perihilar cholangiocarcinoma in patients with primary sclerosing cholangitis: an international multicentre study

Abstract: Background: Resection for perihilar cholangiocarcinoma (pCCA) in primary sclerosing cholangitis (PSC) has been reported to lead to worse outcomes than resection for non-PSC pCCA. The aim of this study was to compare prognostic factors and outcomes after resection in patients with PSC-associated pCCA and non-PSC pCCA.Methods: The international retrospective cohort comprised patients resected for pCCA from 21 centres . Patients operated with hepatobiliary resection, with pCCA verified by histology and with data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The complication rate was higher in PSC but it did not affect post-operative mortality. 328 Surgical resection should be considered in cases where liver transplantation is not possible. Careful evaluation, risk assessment and selection of patients before surgery is crucial and should be carried out by the multidisciplinary team.…”
Section: How Should Gallbladder Polyps Be Managed In Psc?mentioning
confidence: 99%
“…The complication rate was higher in PSC but it did not affect post-operative mortality. 328 Surgical resection should be considered in cases where liver transplantation is not possible. Careful evaluation, risk assessment and selection of patients before surgery is crucial and should be carried out by the multidisciplinary team.…”
Section: How Should Gallbladder Polyps Be Managed In Psc?mentioning
confidence: 99%
“…Despite the fact that our study identified an increased proliferation in PSC-CCA compared with sporadic CCA, a multi-center study recently found no difference in survival after resection between perihilar PSC-CCA and sporadic CCA. 20 Various factors could be involved, including the younger age of PSC-CCA patients, which means they are probably physically more fit with less comorbidity than older patients. The median age of diagnosis of CCA in PSC patients is about 20 years earlier than patients with CCA without PSC.…”
Section: Discussionmentioning
confidence: 99%
“…72 In an era of transplantation oncology, in which PSCassociated pCCA has been considered unresectable, recent data on patients with PSC undergoing liver resection are understandably limited. 66 71 A North American multicentre study from 2018 reported a similar outcome in patients with resectable pCCA with and without PSC, with a 5-year overall survival (OS) and disease-free survival (DFS) of approximately 20%. 73 Lymph node involvement, vascular invasion, low tumour differentiation and higher age are associated with worse OS.…”
Section: Liver Resectionmentioning
confidence: 99%
“…65 66 Even so, radicality is difficult to obtain, morbidity is high and long-term survival remains low with a reported 5-year survival ranging from 20% to 40%. [65][66][67][68] Patients with resected BTC are offered 6 months of adjuvant chemotherapy with capecitabine, according to current guidelines. 69 70 Due to the underlying parenchymal liver disease and the propensity of skip cancer lesions, liver resection in PSC-pCCA is even more challenging, often resulting in narrow margins despite extended resection and the high morbidity and mortality that it entails.…”
Section: Liver Resectionmentioning
confidence: 99%